Optimalisasi Pembuatan Desain Logo Kemasan di Desa Branjang Sebagai Upaya Penguatan Brand Awareness bagi Produk UMKM Memasuki Digital Marketing - Andhi Wijayanto; Moh Khoiruddin; Syam Widia; Salsabila Nadianisa Maruto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Villages, unique regional units with their own systems, need to pay attention to how the entire system supports village development, one of which is in the economic sector. Villages have much potential, one of which is selling typical village products. Brand Awareness will help villages market their products and improve the village economy. Branjang Village already has several village products, but people still need to learn these products as products belonging to Branjang Village. This community service aims to educate village communities on the importance of brand awareness, primarily through creating an attractive logo. The method used in this service is sharing knowledge in group coaching, which produces logo designs for village product packaging. The community understands how important brand and logo awareness is and its impact on product sales and realizes that if their product is developed, it will be able to expand marketing and increase village income.